2022
DOI: 10.3390/ijerph192114473
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Identity Status in Chinese Emerging Adults with and without Hearing Impairment: Latent Profiles and Relationships with Self-Esteem and Subjective Well-Being

Abstract: This study aimed to (1) explore the configuration of vocational identity status among emerging adults with and without hearing impairment using latent profile analysis, and (2) investigate the relationships between vocational identity status and self-esteem and subjective well-being. In total, 408 students without disabilities and 432 with hearing impairments from two Chinese higher institutions participated in the study. The Vocational Identity Status Assessment, Rosenberg Self-Esteem scale, Satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Parents are worried about education, career and job opportunities for their CWHI. When child enters in adolescent it is natural to think about future and career planning (Yuan, et al, 2022). It is important that parents think about future planning of their CWHI.…”
Section: Educational Challenges For Students With Hearing Impairmentmentioning
confidence: 99%
“…Parents are worried about education, career and job opportunities for their CWHI. When child enters in adolescent it is natural to think about future and career planning (Yuan, et al, 2022). It is important that parents think about future planning of their CWHI.…”
Section: Educational Challenges For Students With Hearing Impairmentmentioning
confidence: 99%
“…In addition, recent studies have shown that high levels of subjective well-being (SWB), a protective factor against NSSI, can change adolescents’ strategies of coping with negative emotions, which may reduce the occurrence of NSSI ( 19 ). In particular, SWB is negatively correlated with negative emotions, and adolescents with higher SWB have fewer psychological problems ( 20 ). SWB involves positive emotion and is an overall assessment of one’s perceived quality of life.…”
Section: Introductionmentioning
confidence: 99%